In vitro and in vivo Metabolism of a Potent Inhibitor of Soluble Epoxide Hydrolase, 1-(1-Propionylpiperidin-4-yl)-3-(4-(trifluoromethoxy)phenyl)urea - Wan, Debin; Yang, Jun; McReynolds, Cindy B.; Barnych, Bogdan; Wagner, Karen M.; Morisseau, Christophe; Hwang, Sung Hee; Sun, Jia; Blöcher, René; Hammock, Bruce D. (Frontiers in Pharmacology, 2019)
1-(1-Propionylpiperidin-4-yl)-3-(4-(trifluoromethoxy)phenyl)urea (TPPU) is a potent soluble epoxide hydrolase (sEH) inhibitor that is used extensively in research for modulating inflammation and protecting against hypertension, neuropathic pain, and neurodegeneration. Despite its wide use in various animal disease models, the metabolism of TPPU has not been well-studied. A broader understanding of its metabolism is critical for determining contributions of metabolites to the overall safety and effectiveness of TPPU. Herein, we describe the identification of TPPU metabolites using LC-MS/MS strategies. Four metabolites of TPPU (M1–M4) were identified from rat urine by a sensitive and specific LC-MS/MS method with double precursor ion scans. Their structures were further supported by LC-MS/MS comparison with synthesized standards. Metabolites M1 and M2 were formed from hydroxylation on a propionyl group of TPPU; M3 was formed by amide hydrolysis of the 1-propionylpiperdinyl group on TPPU; and M4 was formed by further oxidation of the hydroxylated metabolite M2. Interestingly, the predicted α-keto amide metabolite and 4-(trifluoromethoxy)aniline (metabolite from urea cleavage) were not detected by the LC-MRM-MS method. This indicates that if formed, the two potential metabolites represent <0.01% of TPPU metabolism. Species differences in the formation of these four identified metabolites was assessed using liver S9 fractions from dog, monkey, rat, mouse, and human. M1, M2, and M3 were generated in liver S9 fractions from all species, and higher amounts of M3 were generated in monkey S9 fractions compared to other species. In addition, rat and human S9 metabolism showed the highest species similarity based on the quantities of each metabolite. The presence of all four metabolites were confirmed in vivo in rats over 72-h post single oral dose of TPPU. Urine and feces were major routes for TPPU excretion. M1, M4 and parent drug were detected as major substances, and M2 and M3 were minor substances. In blood, M1 accounted for 9.6% of the total TPPU-related exposure, while metabolites M2, M3, and M4 accounted for <0.4%. All four metabolites were potent inhibitors of human sEH but were less potent than the parent TPPU. In conclusion, TPPU is metabolized via oxidation and amide hydrolysis without apparent breakdown of the urea. The aniline metabolites were not observed either in vitro or in vivo. Our findings increase the confidence in the ability to translate preclinical PK of TPPU in rats to humans and facilitates the potential clinical development of TPPU and other sEH inhibitors.